Celebrating Mary Herrick's Birthday at Fresno County Counsel - Watkins, Howard::::::::: (1988)
County Counsel Max Robinson on right speaking; l to r: Tom Riggs, Sharon St. John, Debbie Lucas, Barbara Christiansen, Mary Herrick, James Waterman, Ursula Bufe, Max Robinson